Data-driven climate-smart strategies for boosting crop yield and minimizing greenhouse gas emissions by optimizing cropping systems and fertilization practices - Wentao Wu (PLoS ONE, 2026)
The conflict between food production and environmental protection calls for climate-smart agricultural solutions. This study investigated data-driven climate-smart strategies for optimizing cropping systems and nitrogen management to increase crop yield and cut greenhouse gas emissions in China’s Beijing-Tianjin-Hebei (BTH) region, which is grappling with pronounced climatic and environmental challenges. The study evaluated three cropping systems: spring maize monoculture (M), winter wheat followed by summer maize double-cropping (WM), and a triple-cropping system encompassing winter wheat, summer maize, and spring maize (WMM). Additionally, four nitrogen fertilization treatments were assessed to understand their impacts. The crop climate resilient index was created to identify the optimal management practices. Leveraging the Agricultural Production Systems sIMulator (APSIM) model, this study simulated the daily dynamics of crop yields, soil organic carbon (SOC) content, and nitrous oxide (N₂O) emissions over a comprehensive 40-year period spanning from 1981 to 2020. The findings revealed intriguing insights into SOC dynamics and nitrogen fertilizer efficiency. Across all cropping systems, the SOC content augmented with increased nitrogen application, with peak levels reaching 294.9 kg·ha ⁻ ¹ under the highest fertilization treatment. The N₂O emissions displayed an upward trend over time, positively correlated with escalating fertilizer use. Regarding crop yields, higher nitrogen inputs generally correlated with enhanced productivity. Overall, the WM system, when coupled with F2 treatment (90 kg·ha ⁻ ¹ for wheat and 60 kg·ha ⁻ ¹ for maize), emerged as the optimal scenario, achieving the highest climate resilient index value of 0.65. These findings underscore the profound importance of integrating cropping systems with judicious nutrient management in developing agricultural systems that are adaptive, productive, and environmentally sustainable. By adopting such practices, farmers in the BTH region and similar climates can achieve agricultural clean production that is robust enough to withstand climate variability and contribute to global efforts towards food security and ecological preservation. As the climate continues to evolve, the precision and holistic application of these strategies will be crucial in maintaining the vitality and productivity of agricultural landscapes.